2017
DOI: 10.4103/sja.sja_112_17
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided continuous spinal anesthesia for cesarean section in a parturient with scoliosis corrected with harrington's rod surgery

Abstract: With rapid improvement in healthcare in Saudi Arabia, increasing number of women with surgically corrected kyphoscoliosis are likely to present for cesarean section (CS) or vaginal delivery requiring anesthesia or analgesia. Despite the surgical correction, these patients have poor cardiopulmonary reserves which increase the risks associated with general anesthesia. Whereas altered vertebral anatomy from previous surgery and the presence of metal work in spine make performing of regional anesthesia (RA) diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Pre-puncture ultrasound examinations can provide crucial information such as the identification of the midline of the spine, precise intervertebral space, prediction of the depth of the epidural space, and determination of the needle insertion angle. This has established ultrasound guidance as a key tool for delivering high-quality healthcare [ 20 , 21 ]. Particularly in cases where patients are obese or palpation for landmarks is difficult, the use of ultrasound-guided punctures can reduce the risk of vascular puncture and decrease the incidence of postpartum back pain and headaches, demonstrating its significant advantages in enhancing safety [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-puncture ultrasound examinations can provide crucial information such as the identification of the midline of the spine, precise intervertebral space, prediction of the depth of the epidural space, and determination of the needle insertion angle. This has established ultrasound guidance as a key tool for delivering high-quality healthcare [ 20 , 21 ]. Particularly in cases where patients are obese or palpation for landmarks is difficult, the use of ultrasound-guided punctures can reduce the risk of vascular puncture and decrease the incidence of postpartum back pain and headaches, demonstrating its significant advantages in enhancing safety [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lavelle et al reported on 2 patients who received epidural anesthesia for CS after anterior spinal surgery (25). Majeed et al and Yeo et al reported that spinal anesthesia was successfully performed in parturients with scoliosis corrected with Harrington's rod surgery (26,27). Most parturients may benefit more from neuraxial anesthesia than from GA (24), and therefore, we chose neuraxial anesthesia for CS in parturients after lumbar fracture operations.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that US is helpful in identifying the puncture site and measuring the puncture depth when performing neuraxial techniques, which increases the success rate, particularly in technically difficult cases (24,(36)(37)(38)(39). Preprocedural US scanning of the spine may reduce the risk of technical difficulties in patients with a previous history of lumbar surgery (26,27,40). The spinal pedicle screw and rod fixation system can be easily recognized as strong reflectors in the median transverse and paramedian sagittal views.…”
Section: Discussionmentioning
confidence: 99%
“…also removed catheter after surgery and the patient did not develop postdural puncture headache. [7]…”
mentioning
confidence: 99%